Akibat Hukum Putusnya Perkawinan Karena Perceraian - Simamora, Sovia Febrina Tamaulina; Siregar, Ria Juliana; Situmorang, Samuel; Gultom, Meli Hertati (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2025)
Divorce is the end of the relationship between husband and wife which is legal according to law. The termination of the marriage relationship has legal consequences for the position, rights and obligations of husband and wife and children, and is also included in joint assets. Joint property is property obtained by a husband and wife during marriage. This joint property arises from customs which are the provisions governing the husband and wife's property to be made into joint property with the aim of building a household and binding themselves to each other. This research uses normative legal research methods, namely methods that specifically reflect the identity of the legal discipline as a science. Library research takes precedence. The reason for using normative research is that this research refers to legal norms contained in laws and regulations and norms that apply and bind society. The approach used in this research is a statutory approach related to making inheritance certificates. The type of research used in this research is descriptive analytical research, where this research aims to provide a solution to problems that arise precisely and in depth.